Analysis of The Implementation of Sustainable Food Agricultural Land Protection Policy in Bandung District: A Case Study of Rice Field Conversion in Cikancung District - Hanggas Wirapradeksa (Publikasi Indonesia, 2024)
The policy of sustainable protection of agricultural land becomes crucial in addressing land degradation and land use conversion, especially from agriculture to non-agriculture, alongside the increasing demand for land due to population growth and economic development, which can lead to negative impacts such as a decrease in food security, marginalization of agricultural land, and an increase in flood risks. This research aims to analyze the implementation of the Sustainable Protection of Food Agricultural Land Policy, understand the rate of paddy field conversion, and identify trends in land conversion after the policy's enforcement. This study employs a qualitative approach, with data obtained through interviews, observations, and documentary studies. The research is conducted in Bandung Regency, with samples taken from Cikancung Sub-district, Bandung Regency, West Java Province. Informants involved in this research are selected through judgment sampling and are individuals related to the sustainable protection of agricultural land policy and relevant stakeholders. Data analysis is conducted using qualitative and spatial analysis. The research findings indicate that the implementation of sustainable agricultural land protection policy in Bandung Regency is still in the socialization and planning stages. Based on spatial analysis, the implementation of the policy in Cikancung Sub-district has led to the conversion of paddy fields, particularly in non-technical irrigation paddy fields, predominantly converted into industrial land. This conversion covers a total area of 20.3 hectares, with the most significant change occurring in non-technical irrigation paddy fields converted into industries, covering an area of 13.7 hectares. Based on internal, external, and policy analysis, it can be concluded that the policy implementation in Cikancung Sub-district has not been optimal in addressing the conversion of paddy fields.